2023
DOI: 10.1021/acschembio.3c00255
|View full text |Cite
|
Sign up to set email alerts
|

Isonitrile-Tetrazine Click-and-Release Chemistry for Controlling RNA-Guided Nucleic Acid Cleavage

Abstract: With the increasing demand for the regulation of CRISPR systems, a considerable number of studies have been conducted to control their excessive activity levels. In this context, we propose a method that involves a bioorthogonal cleavage reaction between isonitrile and tetrazine to modulate the cleavage activity of the CRISPR system. Importantly, isonitrile demonstrates significant potential for modifying sgRNAs, making it a promising candidate for bioorthogonal reactions, a phenomenon that has not been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The approach is also based on the “RNA cloaking” strategy recently developed by Kool and co-workers. , The strategy utilizes acylimidazole reagents to reversibly modify the 2′–OH groups of functional RNAs, which results in blocking of RNAs’ folding, hybridization, and protein interactions. A number of different cloaking reagents have been reported in recent years. , Subsequent uncloaking has been accomplished using light, nucleophiles, or phosphine reagents. The reversible acylation strategy has been shown to enhance the RNA stability by protecting it from chemical and enzymatic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The approach is also based on the “RNA cloaking” strategy recently developed by Kool and co-workers. , The strategy utilizes acylimidazole reagents to reversibly modify the 2′–OH groups of functional RNAs, which results in blocking of RNAs’ folding, hybridization, and protein interactions. A number of different cloaking reagents have been reported in recent years. , Subsequent uncloaking has been accomplished using light, nucleophiles, or phosphine reagents. The reversible acylation strategy has been shown to enhance the RNA stability by protecting it from chemical and enzymatic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The current strategy places an aromatic group directly on the 2'-OH position, which has not been possible previously (Figure 1a). Since polyacylation has been shown to be useful for stabilizing and caging RNA, [17][18][19][20][21][22] it seems possible that polyarylation may also provide similar types of benefits and applications; more work will be needed to explore this possibility. In any case, the new reagents provide stable ether bonds to RNA, structurally distinct from prior adducts.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] To date, most modifications have been incorporated during chemical or enzymatic synthesis of the polymers; however, recent work has been aimed at modifications that can be introduced post-synthesis, [6][7][8][9] which can offer benefits of ease of use, lower cost, and rapid implementation. Chemical probes that react with RNA are broadly employed for multiple applications, including labeling, [10,11] isolation, [4,12] probing folded structure, [13][14][15][16] controlling RNA function, [17][18][19][20][21] stabilizing the polymer against strand cleavage, [22] and assessing RNA-small molecule interactions. [23][24][25][26] Post-synthetic reactions of RNA can take place on RNA bases or at 2'-OH groups.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Recent studies demonstrated that RNA structure and function could be destroyed by 2'-OH group acylation ('cloaking') using acylimidazole reagents, and efficiently reinstated with a removal of acylation adducts ('uncloaking') upon the external addition of chemical reagents, representing a promising strategy for external control over the function of RNA and gRNA in CRISPR systems. [43][44][45][46][47][48][49][50] It is conceivable that the gRNA function can be temporarily suspended by attaching photolabile groups (PLGs) on 2'-OH group, and subsequently restored by light irradiation. In view of this, Zhou and Tian group adopted RNA 2'-OH acylation to develop photo-controlled CRISPR-Cas9 system for genome editing in human cells.…”
Section: Introductionmentioning
confidence: 99%